Antifungal Volatilomes Mediated Defense Mechanism against Fusarium oxysporum f. sp. lycopersici, the Incitant of Tomato Wilt - Praveen Thangaraj; Akshaya Subbaih Balamurali; Krishnamoorthy Akkanna Subbiah; Nakkeeran Sevugapperumal; Thiribhuvanamala Gurudevan; Sivakumar Uthandi; Haripriya Shanmugam (Molecules, 2022)
In this study, the volatilomes of naturally growing plant leaves were immobilized in a suitable substrate to enhance vapors’ diffusion in the soil to eradicate the Fusarium wilt pathogens in Tomato. Volatilomes produced by Mentha spicata leaves immobilized in vermiculite ball was found to be effective and exhibit 92.35 percent inhibition on the mycelial growth of Fusarium oxysporum f. sp. lycopersici (FOL). Moreover, the volatilomes of M. spicata immobilized vermiculite balls were tested based on the distance traveled by the diffused volatilomes from the ball and revealed that the volatilomes of M. spicata traveled up to 20 cm distance from the center of PVC (Polyvinly chloride) chamber showed maximum reduction in colony growth of FOL at 12th day after inoculation. Tomato plants inoculated with FOL revealed increased expressions of defense gene, pathogenesis related protein (PR1) with 2.63-fold after 72 h and the gene, transcription factor (WRKY) increased with 2.5-fold after 48 h on exposure to the volatilomes of M. spicata vermiculite balls. To the best of our knowledge, this is the first report on development of volatilomes based vermiculite ball formulations. This result indicated that the volatilomes of M. spicata are promising phyto-fumigants for management of Tomato Fusarial wilt.